IMPLEMENTATION OF ONLINE MODULE BASED THINK PAIR SHARE DURING COVID 19 PANDEMIC - Giantari,, Devinda Naufal; Sumardi, Kamin; Sukandar, Aan (Universitas Pendidikan Indonesia, 2020)
This research aims to acquire online learning module TPS-based. This module will be used in the online learning process to ensure a long distance study in the Covid-19 pandemic. The research methods used are research and deveopment (RD) consisting of 6 steps of preliminary analysis, curriculum analysis, writing and drafting of teaching materials, product trials, revisions, and final products. The research instruments used are polls andsheet validations. Module validation is done by material and media experts. Respondents to this study were students of SMK grade XI majoring engineering cooling and air conditioners as many as 20 students. The results showed that according to the materialexperts of this module already meet the requirements of a good module of the aspect of content feasibility and feasibility of presentation with a value of: 85.23%. According to the media experts the module has fulfilled the requirements of a good module of the content feasibility aspect and language eligibility with a value of 80.88%. This module is in positive response by students with an average percentage of 85% covering the aspect of the material, the aspect of the language, the aspect of interest and the aspect of the display. The conclusion of this research is that the TPS-based online learning module is well worth the use and has fulfilled good module standards. In addition, this module can be used in the online learning process especially in the Covid-19 pandemic.